L’assurance-grève et le courtier d’assurance - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1986)
Strike insurance, as described by our contributor, is real. It already exists for major American and Canadian newspapers through a mutual insurance company in Bermuda. Strike insurance enables the insured to meet part of the losses incurred during a strike. However, very few companies write this type of insurance. Above all, a company head must not feel protected to a point where, as long as major costs are covered, it does not matter if profits are not. To organize this type of insurance, it is important to be selective and avoid those companies, which regularly go on strike and have enough insureds to provide the companies specializing in strike insurance with the necessary resources.